2013
DOI: 10.4049/jimmunol.1301430
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Targeting Inhibitory Fcγ Receptor IIB (CD32b) in the Mouse Is Limited by Monoclonal Antibody Consumption and Receptor Internalization

Abstract: Genetic deficiency of the inhibitory Fc receptor, FcγRIIB (CD32b), has been shown to augment the activity of activatory FcγR and promote mAb immunotherapy. To investigate whether mAbs capable of blocking FcγRIIB have similar capacity, we recently generated a panel of specific anti-mouse FcγRIIB mAbs that do not cross-react with other FcRs, allowing us to study the potential of FcγRIIB as a therapeutic target. Previous work revealed a number of these mAbs capable of eliciting programmed cell death of targets, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 72 publications
(67 reference statements)
2
23
0
Order By: Relevance
“…We previously explored an equivalent panel of mFcgRII-specific mAbs (Williams et al, 2012) and observed that they had limited therapeutic benefit due to their rapid consumption in vivo (Williams et al, 2013b). Similar rates of internalization were not seen on human target cells, at least in vitro, in agreement with earlier studies (Rankin et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…We previously explored an equivalent panel of mFcgRII-specific mAbs (Williams et al, 2012) and observed that they had limited therapeutic benefit due to their rapid consumption in vivo (Williams et al, 2013b). Similar rates of internalization were not seen on human target cells, at least in vitro, in agreement with earlier studies (Rankin et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…A panel of validated reagents is extremely valuable in assessing the importance of individual FcgR expression levels in diseases in which they are proposed to be modulated. We recently demonstrated that expression of the inhibitory hFcgRIIB accelerates the internalization of rituximab (42) and other mAb (43) from the surface of B cells in a dose-dependent manner that limits their therapeutic efficacy (42,(44)(45)(46). A careful assessment of hFcgRIIB levels in the blood of patients receiving a therapeutic mAb may be an important biomarker of prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…ADCP with THP-1 cells and rituximab was also blocked with anti-FcgRI and anti-FcgRII mAbs but not with an anti-FcgRIII mAb (25). THP-1 cells express FcgRIIB as well as FcgRIIA (26), and FcgRIIB inhibits FcgRIA/IIA-mediated phagocytosis (27). However, it is unknown how the inhibitory FcgRIIB is involved in our ADCP system as compared with FcgRIA and FcgRIIA.…”
Section: Discussionmentioning
confidence: 89%